Growth components and zinc recovery efficiency of upland rice genotypes - Fageria,Nand Kumar (2005)
The objective of this work was to evaluate Zn use efficiency by upland rice genotypes. The experiment was carried out in a greenhouse, with ten upland rice genotypes grown on an Oxisol (Typic Hapludox) with no application, and with application of 10 mg kg-1 Zn, applied as zinc sulfate. Shoot dry weight, grain yield, Zn harvest index, Zn concentration in shoot and in grain were significantly influenced by soil Zn levels and genotypes. However, panicle number and grain harvest index were significantly affected only by genotype. Genotypes CNA8557, CNA8540 and IR42 produced higher grain yield than other genotypes. Genotypes showed significant variability in Zn recovery efficiency. On average, 13% of the applied Zn was recovered by upland rice genotypes. Genotypes with high Zn recovery efficiency could be used in breeding of Zn efficient upland rice cultivars. Higher level of soil Zn (10 mg kg-1) increased significantly the concentrations of plant Cu and Mn. However, Fe concentrations in plant (shoot and grain) were not influenced by soil Zn levels.